A new record of the freshwater polychaete Namanereis hummelincki (Polychaeta: Nereididae) from epigean waters of Montserrat - Shoobs, Nathaniel F.; Schmidt, Robert E.; Mcmullin, Erin R. (Zootaxa, 2016)
The presence of the freshwater polychaete, Namanereis hummelincki (Augener), on Montserrat is documented for the first time. Although collected in the sediment of a freshwater stream, this subterranean species most likely lives in groundwater aquifers. A mitochondrial cytochrome c oxidase subunit I (COI) sequence obtained from this material supports assignment to the genus Namanereis Chamberlin, and morphological analysis supports identification as N. hummelincki. Differences in jaw morphology observed in the Montserrat specimens may indicate long-term separation from other Caribbean island populations.